Does anti-reflux surgery control Barrett’s oesophagus progression? - Alghazzawi, Ali J.; Khabaza, Ali A.; Al-Hijaji, Mohammed H. (International Surgery Journal, 2018)
Controversy exists as to whether or not anti-reflux surgery can prevent the potential long-term complications of Barrett’s oesophagus, in particular, dysplastic changes. Hence, literature was reviewed to find out effects of anti-reflux surgery on patients with Barrett’s oesophagus. Data has been analysed using different electronic database including Ovid Medline, Scopus, Google Scholar and PubMed. Anti-reflux surgery is considered an effective option for rapid and long-term control of reflux symptoms. Most patients who were included in the studies had a satisfactory control of their symptoms after surgery. Successful procedures effectively abolished gastric reflux in the majority of patients. On the other hand, there were different patterns of Barrett’s oesophagus segment progression after surgery regardless of the procedure’s success. Many patients developed de novo Barrett’s oesophagus, at the same time the intestinal metaplasia regressed in other patients, but the Barrett segment has remained unchanged in the majority of patients. Similarly, the pattern of dysplasia progression was different among patients. Surgery was effective in producing dysplasia regression in many patients, but it failed to prevent progression of columnar intestinal metaplasia into dysplasia in other patients. In conclusion the potential long-term complications of Barrett’s oesophagus can develop after anti-reflux surgery. Therefore, long life follow- up, after surgery, is mandatory.